PEMAHAMAN HUKUM PADA PENDIDIKAN ANTI KORUPSI PERSFEKTIF NILAI-NILAI PANCASILA (Faculty of Law, University of Palembang, 2022)
In the face of today's era, there are many shifts from behavioral values ​​that occur in life in society, decreasing moral values ​​that deviate from cultural values ​​in society. Pancasila which is extracted from the cultural values ​​of the community is a form of guidance in people's lives in the nation and state. One of the cultural values ​​of society that are contrary to the values ​​of Pancasila is the emergence of a culture of corruption that occurs in various fields of people's lives, so that it can have a detrimental impact on the community, towards the goals and ideals of the state, as a realization of the implementation of values. values ​​in the precepts of Pancasila. In response to this, it is necessary to provide a form of solution, in order to overcome corruption cases that occur by giving a form of strength in realizing the function of Pancasila values ​​in the form of application, in the implementation of social life, starting from the lowest society to the highest society. This research aims is to function the values ​​of Pancasila in their realization as a guide in the behavior of society, in an effort to prevent it is to provide a form of education in schools to higher education and provide a form of socialization in the form of seminars in organizational activities. social institutions Institutions The methodology in this study is a qualitative descriptive and normative qualitative methodology, examining the Corruption law and collecting data based on information from electronic media and also in the latest books and journals. The results of the study show that there is still a weak understanding of Pancasila values, including in enforcement Laws and laws are still not used as a means to be guided, in an effort to handle corruption cases